2020
DOI: 10.3390/nu12113410
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and/or Genistein Treatment Impact Gut Microbiota and Inflammation after 12 Weeks on a High-Fat, High-Sugar Diet in C57BL/6 Mice

Abstract: Genistein (Gen) and exercise (Exe) have been postulated as potential strategies to ameliorate obesity, inflammation, and gut microbiota (GM) with promising results. However, the impact of the combination of both Exe and Gen is yet to be investigated. We aimed to analyze the impacts of Exe, Gen, and their combined effects on GM and inflammation in mice after a 12-week high-fat, high-sugar diet (HFD). Eighty-three C57BL/6 mice were randomized to control, HFD, HFD + Exe, HFD + Gen, or HFD + Exe + Gen. The V4 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 94 publications
(144 reference statements)
2
19
0
Order By: Relevance
“…Six animal studies reported energy intake (37,38,43,45,49,51) and two studies reported energy expenditure (38,43), respectively. Besides, 18 (23,35‐45,47,49‐53) of the 21 animal studies were randomized studies, whereas the other 3 were longitudinal intervention and nonrandom control studies (24,46,48).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six animal studies reported energy intake (37,38,43,45,49,51) and two studies reported energy expenditure (38,43), respectively. Besides, 18 (23,35‐45,47,49‐53) of the 21 animal studies were randomized studies, whereas the other 3 were longitudinal intervention and nonrandom control studies (24,46,48).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 14 of the 21 animal studies reported a significant weight‐lowering effect of exercise (23,24,35,37,38,40,42‐44,47‐51). Five animal studies reported unchanged body weight (36,39,41,46,53), and two reported increased body weight (45,52).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it has long been speculated that exercise is linked to an altered GM. Recent animal studies have shown that exercise training can modify the gut of rodents and their associated gut microbiome [ 9 ] [ 10 ]. A study also found that exercise training can alter GM of those with an obese and hypertensive phenotype.…”
Section: Effects Of Pa On Gmmentioning
confidence: 99%